Infection prevention and control and antibiotic stewardship practices in pediatric long-term care facilities. (19th November 2019) - Johnson, Candace L.; Hill-Ricciuti, Alexandra; Grohs, Emily; Saiman, Lisa
Abstract: Pediatric long-term care facilities were surveyed to assess infection control and antimicrobial stewardship practices. Policies mandated by the Centers of Medicare and Medicaid Services (CMS) were included. Only 40% of sites reported implementing >90% of surveyed CMS policies. The survey also identified several gaps in non–CMS-mandated policies.